Resonant tunneling : quantum waveguides of variable cross-section, asymptotics, numerics, and applications /: quantum waveguides of variable cross-section, asymptotics, numerics, and applications. ([2015]) - Baskin, Lev; Neittaanmäki, P (Pekka); Plamenevskiĭ, B. A; Sarafanov, Oleg
No abstract available